Adjacent combustion heat release and emissions over various load ranges in a premixed direct injection diesel engine: A comparison between gasoline and ethanol port injection. (15th March 2022) - Tongroon, Manida; Chuepeng, Sathaporn
Abstract: In a premixed diesel engine, supplementary fuels (gasoline and ethanol) are individually premixed by port fuel injection prior to induction and combustion in the main diesel-injected combustion chamber. This study compared emissions and heat release patterns adjacent to the combustion stroke of a premixed diesel engine. A single-cylinder direct injection diesel engine was examined by varying the ratios of the supplementary fuel to diesel quantity to meet the set loads. The engine's target speed was 1600 rpm, and the brake mean effective pressures of 2, 5, and 7 bar were loads representing low-, medium-, and high-load operations, respectively. Results show that the gasoline premixture yielded higher thermal efficiency than the ethanol premixture. When the quantity of gasoline supplementary fuel increased, the thermal efficiency increased, whereas the opposite trend was observed with ethanol. The combustion phasing was delayed by increasing both supplementary fuel ratios. Quantities of nitrogen oxides, smoke, and total unburned hydrocarbon were reduced, and carbon monoxide increased with the elevated quantity of port-injected fuel. The ethanol–diesel dual fuel is advantageous regarding smoke opacity, but it suffers from nitrogen oxides trade-off. Graphical abstract: Image 1 Highlights: Gasoline and ethanol port fuel injection comparison for diesel dual fuel engine. Supplementary fuel ratio influence on engine behaviors, combustion and emissions. Combustion analysis of a single-cylinder engine over load range at constant speed. Assessment of specific fuel consumption and brake thermal efficiency. Comparative exploration of gaseous CO, HC, NOx emissions and smoke opacity.